2006
DOI: 10.1645/ge-666r.1
|View full text |Cite
|
Sign up to set email alerts
|

A New Myxozoan From Feral Goldfish (Carassius Auratus)

Abstract: In February 2004, a mass die-off of common goldfish Carassius auratus L., presumptively caused by bacterial coldwater disease (Flavobacterium psychrophilum), occurred at Fern Ridge Reservoir, Oregon. A range of size classes was affected, but all mature fish were female and all fish were infected with a single myxozoan, Chloromyxum auratum n. sp. No histological changes were observed associated with the parasite. Infection was represented by mictosporic plasmodia and free-floating spores in the gall bladder. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…ellipsoidal spores with 2 shell valves, 4 equal-sized polar capsules and a bundle of caudal filamentous projections, shows the characters of a parasite belonging to the genus Chloromyxum (Lom & Noble 1984, Lom & Dyková 2006. A comparison of our results with the morphology and ultrastructural organization of previously described species of this genus, shows that the morphology is similar, which consequently confirms that this parasite belongs to this genus (Lom & Noble 1984, Lom et al 1988, Baska 1990, 1993, Molnár 1992, Shul'man & Ieshko 2003, Hallett et al 2006, Lom & Dyková 1992, 2006, although few of the previously described species have attached caudal filaments. Amongst the 115 recognized species of this genus, only Chloromyxum leydigi Mingazzini, 1890 (Pinto 1928, Gioia & Cordeiro 1996, C. ovatum and C. transversocostatum (Kuznetsova 1977) have attached filaments (Lom & Dyková 2006).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…ellipsoidal spores with 2 shell valves, 4 equal-sized polar capsules and a bundle of caudal filamentous projections, shows the characters of a parasite belonging to the genus Chloromyxum (Lom & Noble 1984, Lom & Dyková 2006. A comparison of our results with the morphology and ultrastructural organization of previously described species of this genus, shows that the morphology is similar, which consequently confirms that this parasite belongs to this genus (Lom & Noble 1984, Lom et al 1988, Baska 1990, 1993, Molnár 1992, Shul'man & Ieshko 2003, Hallett et al 2006, Lom & Dyková 1992, 2006, although few of the previously described species have attached caudal filaments. Amongst the 115 recognized species of this genus, only Chloromyxum leydigi Mingazzini, 1890 (Pinto 1928, Gioia & Cordeiro 1996, C. ovatum and C. transversocostatum (Kuznetsova 1977) have attached filaments (Lom & Dyková 2006).…”
Section: Discussionsupporting
confidence: 81%
“…C. cyprini (AY604198) and C. legeri (AY604197) were found in the gall bladder of Hypophthalmichthys molitrix and Cyprinus carpio, respectively, from the Czech Republic (Fiala & Dyková 2004). C. auratum (AY971521) and C. trijugum (AY954689) were found in the gall bladder of Carassius auratus and Pomoxis nigromaculatus, respectively, from Oregon, USA (Hallett et al 2006). C. truttae (AJ581916) was found in the gall bladder epithelium and C. schurovi (AJ581917) in kidney tubules of Salmo salar in Scotland (Holzer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, this species is a widespread invasive and continues to be introduced into the wild through escape from hatcheries and ponds, release from aquaria, and disposal of bait fish (Nico et al 2014). A survey of goldfish from a national USA pet store chain, revealed that 50 % of fish were infected with up to three species of six myxozoans, representing Sphaerospora, Myxobolus, Hoferellus, and Zschokkella (see Hallett et al 2006b). Species of the first three genera were also observed in fish sampled directly from an Arkansas goldfish farm (Karandashova 2008): Sphaerospora sp., Myxobolus diversus, Myxobolus cultus, and Hoferellus carassii.…”
Section: Aquatic Pet Tradementioning
confidence: 99%
“…Another species, Chloromyxum auratum, was prevalent in goldfish illegally introduced into an Oregon reservoir, and was thought to have been cointroduced with its vertebrate host since none of the local native fishes was infected. An appropriate invertebrate host must already have been present to sustain infections in the goldfish population (Hallett et al 2006b). Another carp myxozoan, Myxobolus koi, was introduced with its host Cyprinus carpio from Asia to the UK and the USA, and has caused mortalities of koi in ornamental ponds (Crawshaw and Sweeting 1986;Camus and Griffin 2010).…”
Section: Aquatic Pet Tradementioning
confidence: 99%